Diagnostic Value of Vessel Wall Imaging to Determine the Timing of Extracranial‒Intracranial Bypass for Moyamoya Syndrome Associated with Active Sjögren's Syndrome: A Case Report - Shindo, Takafumi; Ito, Masaki; Sugiyama, Taku; Okuyama, Tomohiro; Kono, Michihito; Atsumi, Tatsuya; Fujimura, Miki (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Sjögren's syndrome is a chronic autoimmune disorder that predominantly affects exocrine organs. It is characterized by an organ-specific infiltration of lymphocytes. The involvement of the major cerebral arteries in Sjögren's syndrome has rarely been reported. A recent study reported a case of successful extracranial–intracranial (EC–IC) bypass without complications, even in the active inflammatory state, although the optimal timing of such a bypass remains unclear.Case Description We here report the case of a 43-year-old woman presenting with acute ischemic stroke due to progressive middle cerebral artery (MCA) occlusion and signs of primary Sjögren's syndrome. During intensive immunosuppressive therapy for active Sjögren's syndrome, the patient was monitored using contrast-enhanced magnetic resonance vessel wall imaging (MR-VWI). A couple of intravenous cyclophosphamide injections combined with a methylprednisolone pulse and antiplatelet therapy resulted in clear resolution of vessel wall enhancement, which suggested remission of inflammatory vasculitis. Nevertheless, she still experienced a transient ischemic attack (TIA) due to decreased regional cerebral blood flow by MCA occlusion, as demonstrated by the conventional time-of-flight MR angiography and single-photon emission computed tomography. Considering the increased risk of further stroke, the decision was made to perform an EC–IC bypass as a treatment for medically uncontrollable hemodynamic impairment. Her postoperative course was uneventful without further repeated TIAs, and continued immunosuppressive therapy for Sjögren's syndrome provided effective management.Conclusions Our findings emphasize the diagnostic value of contrast-enhanced MR-VWI in monitoring the effect of immunosuppressive therapy for the major cerebral artery vasculitis and in determining the timing of EC–IC bypass as a “rescue” treatment for moyamoya syndrome associated with active Sjögren's syndrome.
Keywords: large cerebral artery; moyamoya syndrome; Sjögren's syndrome; vascular disorder; vessel wall imaging